Stefan Żeromski, czyli biografia wpisana w historię - Załęczny, Jolanta (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
Stefan Żeromski was a prominent writer and a social activist. His biography went down in Polish history. He was particularly active during the war in 1920 and fighting for Polish borders. After the war he popularized the idea of self-government and was strongly supporting regionalism. His work was substantially influenced by pursuit of independence. Żeromski was treating his work as a way to serve the society.